2013
DOI: 10.1186/1476-4598-12-55
|View full text |Cite
|
Sign up to set email alerts
|

Flavokawain B, a kava chalcone, inhibits growth of human osteosarcoma cells through G2/M cell cycle arrest and apoptosis

Abstract: BackgroundOsteosarcoma (OS) is the most common primary bone malignancy with a high propensity for local invasion and distant metastasis. Limited by the severe toxicity of conventional agents, the therapeutic bottleneck of osteosarcoma still remains unconquered. Flavokawain B (FKB), a kava extract, has been reported to have significant anti-tumor effects on several carcinoma cell lines both in vitro and in vivo. Its efficacy and low toxicity profile make FKB a promising agent for use as a novel chemotherapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 36 publications
3
73
0
2
Order By: Relevance
“…A previous study had reported that FKB inhibited proliferation of HCT 116 cells at an IC 50 of 25 μM [16], which is consistent with the present finding. Moreover, FKB has been shown to inhibit 50% cell growth of SK-LMS-1 and 143B cells at a very low concentration of 2.2 μM (1.25 μg/mL) and 1.97 μM (3.5 μg/mL), respectively [17,18]. These IC 50 values are, however 6 fold lower than that observed in colorectal cancer (HT-29 and HCT 116 cells), which in fact, is within acceptable concentration limits.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had reported that FKB inhibited proliferation of HCT 116 cells at an IC 50 of 25 μM [16], which is consistent with the present finding. Moreover, FKB has been shown to inhibit 50% cell growth of SK-LMS-1 and 143B cells at a very low concentration of 2.2 μM (1.25 μg/mL) and 1.97 μM (3.5 μg/mL), respectively [17,18]. These IC 50 values are, however 6 fold lower than that observed in colorectal cancer (HT-29 and HCT 116 cells), which in fact, is within acceptable concentration limits.…”
Section: Discussionmentioning
confidence: 99%
“…(11)(12)(13)(14)(15)(16) Natural products have played a major role in apoptosis induction of osteosarcoma cells. (17,18) Due to the apoptosis induction by these natural products, several apoptosis-related proteins were induced, including Caspase 3, Caspase 7, Caspase 8 and Caspase 9, B cell lymphoma (Bcl)-2 and Survivin, Bcl-2-associated x protein (Bax), p53 upregulated modulator of apoptosis (Puma) and Fas. (18) In our current study, we pursued a further investigation Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies with murine xenograft models have shown that administration of chalcones significantly reduced the tumor volume by inducing apoptosis (3)(4)(5)(6)(7)(8)(9)(10). The tumor specificity of chalcones has been reported in comparing sensitivity of hepatocarcinoma HepG2 cells to normal liver AML12 cells (11); osterosarcoma to bone marrow and smallintestinal epithelial cells (12); murine acute lymphoblastic leukemia cells L-1210 to normal human lymphocytes (13); and human prostate cancer cells PC3 and DU145 to normal human prostate epithelial cells (14). Although chalcones have been reported to induce apoptosis of human oral carcinoma cell line (HSC-3) (15) and cultured primary and metastatic oral cancer cell lines (16), the tumor specificity against these has not been investigated as far as we are aware of.…”
mentioning
confidence: 99%